If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5y + -12 = 0 Reorder the terms: -12 + 6x + -5y = 0 Solving -12 + 6x + -5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 6x + 12 + -5y = 0 + 12 Reorder the terms: -12 + 12 + 6x + -5y = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 6x + -5y = 0 + 12 6x + -5y = 0 + 12 Combine like terms: 0 + 12 = 12 6x + -5y = 12 Add '5y' to each side of the equation. 6x + -5y + 5y = 12 + 5y Combine like terms: -5y + 5y = 0 6x + 0 = 12 + 5y 6x = 12 + 5y Divide each side by '6'. x = 2 + 0.8333333333y Simplifying x = 2 + 0.8333333333y
| 3x+y=-36 | | 4-x/x+2sqrtx | | 29/24-7/8 | | (y-x-1)dx+(x+y-1)dy=0I | | 7u-16u=0 | | -2,-8=1/2 | | (-2,_8);m=-1/2 | | 11x(13/19) | | (6x)(24)=72 | | 13/19=x/11 | | 103/7x101/2= | | 103/7*101/2 | | 14+5=25 | | 14+5=25 | | 103/7x101/2 | | 5x+200=2x+100 | | 17/12-(1/8 | | 8y^7-12y^5/2y^3= | | 4n-6=5-2n | | -9+n4=-7 | | 8y^7-12y^5/2y^3 | | (x/(x-3))+(4/x) | | (x/x-3)+(4/x) | | 6x^5-4x^3=-1 | | 3x+6y+5-y-9x-7= | | 5(x-5y)=0 | | (1/7)^(2x-5)=49 | | 29x+5=4.7x-7.6 | | 35y^3+16y^2=12y | | 56x+38y=540 | | H=70-4.9x^2 | | 1/(3x)+5/(8x) |